Peran Keluarga Terhadap Pendidikan dan Perkembangan Anak - Dinny Rahmayanty; Harti Zakia Nopitri; Restu Amanda; Uswatun Dwi Hasanah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This article is about how the role of the family in providing education and child development aims to determine the impact of family roles for children. The method used in this study is the study of litiatur. The family is one of the smallest environments and most affects the education and development of children. The role of parents is very important in the education and development of children. Education is an important basic need for children to support their lives, therefore it needs optimal child development in order to fulfill good education. Therefore, the family plays an important role in shaping the personality, knowledge, morals, and positive attitudes of children.